Thyroid follicle development requires Smad1/5- and endothelial cell-dependent basement membrane assembly - Villacorte, Mylah (Development, 2016)
Thyroid follicles, the functional units of the thyroid gland, are delineated by a monolayer of thyrocytes resting on a continuous basement membrane. The developmental mechanisms of folliculogenesis, whereby follicles are formed by the reorganization of a non-structured mass of non-polarized epithelial cells, are largely unknown. Here we show that assembly of the epithelial basement membrane is crucial for folliculogenesis and is controlled by endothelial cell invasion and by BMP-Smad signaling in thyrocytes. Thyroid-specific Smad1 and Smad5 double-knockout (Smad1/5(dKO)) mice displayed growth retardation, hypothyroidism and defective follicular architecture. In Smad1/5(dKO) embryonic thyroids, epithelial cells remained associated in large clusters and formed small follicles. Although similar follicular defects are found in Vegfa knockout (Vegfa(KO)) thyroids, Smad1/5(dKO) thyroids had normal endothelial cell density yet impaired endothelial differentiation. Interestingly, both Vegfa(KO) and Smad1/5(dKO) thyroids displayed impaired basement membrane assembly. Furthermore, conditioned medium (CM) from embryonic endothelial progenitor cells (eEPCs) rescued the folliculogenesis defects of both Smad1/5(dKO) and Vegfa(KO) thyroids. Laminin α1, β1 and γ1, abundantly released by eEPCs into CM, were crucial for folliculogenesis. Thus, epithelial Smad signaling and endothelial cell invasion promote folliculogenesis via assembly of the basement membrane.